52 Leptin Effects on Leydig Stem Cell Differentiation are Specific to Patients BMI. Issue 1 (1st April 2022) - Seetharam, D; Seetharam, D; Qureshi, R; Khodamoradi, K; Parmar, M; Van Booven, D; Vedenko, A; Farber, N; Arora, H; Ramasamy, R
ABSTRACT: Introduction: Adult Leydig cells in the testes are essential for testosterone production. The growth and differentiation of Leydig cells could be affected by paracrine factors released by testicular microenvironment (TME) (Sertoli and peritubular myoid cells). In our recent study, we demonstrated that Leptin, a paracrine factor secreted by TME, is critical for Leydig stem cells (LSCs) differentiation and subsequent testosterone production via its interaction with Leptin receptor on LSCs, followed by downstream regulation of desert hedgehog (DHH) signaling. Although it is well-known that obesity adversely affects male fertility and testosterone production, the endogenous effects of Leptin on Leydig stem cell differentiation and transcription factors genes (TFs) binding to leptin receptor (LEPR) and the mechanism that are specific to patient's BMI (normal, obese and lean men) are understudied. Additionally, the underlying mechanism behind the differential effects of Leptin (if any) is unknown. Therefore, In the present study, we evaluated the impacts and mechanism of Leptin as a paracrine factor on LSC differentiation in patients with different BMI's. Objective: To uncover the mechanism of Leptin as a paracrine factor on LSC differentiation in patients with different BMI's. Methods: A total of 13 men with testicular failure that were subcategorized as obese (BMI >35), normal (BMI 25-30), and lean (BMI <25) underwent testis biopsies. Using an IRB approved protocol, about 10mg of testicular tissue from each of these men were processed for LSC isolation, culture and characterization. After characterization using Flow cytometry and Immunostaining, cells were treated for dose dependent (0, 1, 10 ng/mL respectively) and time dependent (24, 48, 72, and 96 hours) effects of Leptin in the presence or absence of testicular microenvironment. To validate the effects of leptin on DHH, - LSCs were treated with Leptin in the presence of DHH agonists (SAG) and antagonists (Vismodigib). For the functional studies, UCSC genome browser was used to identify the TFs binding the LEPR promoter. The list of TFs was subjected for Enrichr for enrichment analysis. To evaluate the effects of shortlisted TFs on leptin-LEPR, qPCR and western blotting were performed. Furthermore, to validate the specificity of interaction between Leptin-Leptin receptor on LSC differentiation, sorted LSCs were exposed to siRNA against LEPR in the presence of increased dose of Leptin, followed by evaluating the percentage shift in LSCs to ALCs. After treatment, qPCR, western blot and flow cytometry analysis were performed to evaluate the effects of treatment with respective to the BMI levels. RNA sequencing analysis was performed on cells extracted from men with different BMI's, treated with 0, 0.25, 1 and 10ng/ml Leptin to study the signatures specific effects of leptin with respect to patients BMI. For statistical analysis GraphPad Prism (GraphPad Software) were used. All data were presented as the means ± SEM. The statistical significance between two groups were estimated by unpaired two-tailed t test. Results: Results showed that a strong relationship exists between BMI and leptin levels. Immunostaining, flow cytometry and RNA sequencing results showed that in the men with normal BMI, in the presence of low doses of leptin, there was a shift of the testicular cell population towards adult Leydig cells (increased population of cells staining positive for 3BHSD, LHR) and increased DHH signaling (GLI and SMO). On the contrary, at higher concentrations, the positive effects of leptin on cells from men with normal BMI were neutralized. Furthermore, in cells from lean patients, leptin treatment had a consistent, linear and positive impact on LSC differentiation markers and DHH signaling. Moreover, in cells from obese patients, leptin had a consistent, linear and negative impact on LSC differentiation and markers of DHH signaling. Enrichment analysis identified 50 TFs, of which SOX2, SOX8 and SOX9 were enriched for abnormal pituitary function and therefore for hypothalamic pituitary gonadal axis. The role of these TFs on LSC differentiation remained under-explored. RNA sequencing data from cells exposed to different concentrations of Leptin showed an inducing effect of Leptin on SOX2, SOX8 Sox9 respectively. Consequently, with increasing leptin doses SOX2, SOX8 Sox9 protein and expression has been upregulated. Mechanistically, Leptin-LEPR-TFs induced DHH signaling regulates LSCs differentiation in a different manner which is specific to patient's BMI. Conclusions: Our results demonstrate the influence, BMI has on Leptin induced LSC differentiation. These findings suggest the future potential use of Leptin as a personalized therapy for inducing LSC differentiation and overcoming low Testosterone levels. Further studies are necessary to identify potential therapeutic effects of leptin treatment in improving fertility in the setting of leptin resistance and obesity. Financial Support: Supported by the American Urological Association Research Scholar Award to H.A. J.M.H. is supported by NIH grants 1R01 HL137355, 1R01 HL107110, 1R01 HL134558, 5R01 CA136387, 5UM1 HL113460 and Soffer Family Foundation. Disclosure: No